Preparation and characterization of Titanium (Iv}-6xi1je immobilized on Granular activated carbon - Moh Pak Yan (Universiti Malaysia Sabah, 2007)
Titanium (IV) oxide immobilized on granular activated carbon (as Ti02/GAC) was prepared through hydroxide precipitation of Ti02 from titanium tetraisopropoxide followed by dip-coating and annealing at 550°C. Photocatalytic activity of Ti02/GAC suspended in Methylene Blue (MB) aqueous solution had been investigated. It was found that the removal ofMB by Ti02(0.010g)/GACIUV system (Le. 72%) had no significant difference compared to the summation of MB removal by Ti02(0.010g)lPyrexiUV (Le. 36%) and GACIUV system (Le. 42%) systems. However, comparison of the MB removal against the amount of Ti02 shows that the removal was predominantly contributed by the Ti02 that immobilized on the GAC. Furthermore, it was found that the activity of the Ti02/GACIlN system had reached plateau when more than 0.022g of Ti02 was immobilized on 0.5 g of GAC. In contrast, immobilization of 0.01 Og of Ti02 on 0.5 g of GAC had present the highest photocatalytic activity where about 72% of the MB in the aqueous solution (with [MB] = 1 x 10-4 moIL"I) was removed. The pores on the GAC were believed to be able to adsorb the MB molecules and thus increasing the chances of MB degradation by the photoactivated Ti02. Its reaction kinetics was following the pseudo-first order rate law with the rate constant, k, is 0.0100 min"i. It implies that longer reaction time will give higher degree of removal where the MB molecule will continuously adsorb on the GAC then degraded by the photoactivated Ti02, and subsequently desorbed from the GAC.